Academic Procrastination and Academic Stress in Psychology Students - Fong, Tjia Siu (ANIMA Indonesian Psychological Journal, 2012)
The aim of this study was to see the relation between academic procrastination and academic stress on completing final research paper in psychology. Subjects were every psychology student in the 2011/2012 academic year (students from the 2004-2008 generation (N = 157). Data were collected through surveys and inventories, while analysis conducted using Pearson and Spearman correlation technique on SPSS 16.0 for Windows. Results showed a positive and significant correlation between academic procrastination and academic stress. The positive correlation was also found between the three aspects of academic procrastination (frequency, problem, and the desire to reduce) and academic stress. Those correlations were based on the Temporal Motivational Theory (TMT). The three aspects of academic procrastination have a positive correlation with academic stress in the value aspect (task aversiveness) in TMT. This shows that the higher the value score (task aversiveness), the higher the academic procrastination level, resulting in academic stress . Tujuan penelitian ini adalah melihat hubungan antara prokrastinasi akademik dan stres akademik pada penyelesaian skripsi mahasiswa Subjek penelitian ini adalah seluruh mahasiswa psikologi yang sedang menyelesaikan skripsi pada semester gasal 2011/2012 (berasal dari angkatan 2004 hingga 2008 (N = 157). Data diperoleh melalui survei dan inventori, dan dianalisis menggunakan teknik korelasi Pearson dan Spearman program SPSS 16.0 for Windows. Hasil menunjukkan adanya korelasi positif dan signifikan antara prokrastinasi akademik dan stres akademik. Hasil korelasi positif juga didapatkan dari ketiga aspek prokrastinasi akademik (frek- uensi, masalah, dan keinginan mengurangi) dan stres akademik. Hubungan antara prokrastinasi akademik dan stres akademik didasarkan pada Teori Motivasi Temporal (TMT). Ketiga aspek prokrastinasi akademik berkorelasi positif dengan stres akademik melalui aspek value (task aversiveness) pada TMT. Hal ini menunjukkan makin tinggi value (task aversiveness), maka makin tinggi pula prokrastinasi akademik, yang pada gilirannya akan memicu munculnya stres akademik.